The economics of budget deficits - Rowley, Charles Kershaw; Shughart, William F.; Tollison, Robert D. (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2002)
"The Economics of Budget Deficits" provides a comprehensive overview of the scholarly literature exploring the causes and consequences of deficit spending and the public debt. Incorporating classical, Keynesian and public choice analyses of debt-financed public expenditures, the two volumes contain major theoretical and empirical contributions to the debate. They cover such critical fiscal policy issues as the history and measurement of budget deficits, the question of who bears the burden of the public debt, the use of deficits to solve problems of dynamic policy inconsistency and the relative effectiveness of fiscal rules and constitutional constraints as mechanisms for achieving budget balance. The editors provide an authoritative introduction to the two volumes and separate overviews of each of the seven parts. The book is designed to be of use to all scholars and students interested in fiscal policy and for all policymakers.
Includes bibliographical references and index.
rpm 07/09/16
Loans
Keywords: Budget deficits; Deficit financing; Debts, Public